Rising sun over Borneo : the Japanese occupation of Sarawak, 1941-1945 - Ooi, Keat Gin, 1959- (New York, N.Y. : St. Martin's Press, 1999)
The author examines and evaluates the overall impact of the Japanese occupation of Sarawak on the indigenous peoples, the Chinese inhabitants and the minority European community. How each community responded and reacted to Japanese wartime policies is analyzed to gauge to what extent the occupation affected, positively or otherwise, the lives and attitudes of the people concerned. Specifically this book examines whether the Japanese occupation initiated developments that transformed Sarawak's history, and asks if the Japanese occupation of Sarawak was a turning-point in the country's history or merely an interruption in Sarawak's overall development.
Sarawak and its People -- The indigenous inhabitants -- The immigrant Chinese -- The Europeans -- Japanese Pre-War Activities in North-West Borneo -- Japan's southward expansion policy -- Japan's critical oil situation -- Invasion and Occupation -- Facing the enemy: Sarawak's defence preparations -- The invasion -- Tuans dan Mems Lari: The Flight of European Men and Women -- 'The town of Kuching was occupied without any resistance' -- Under the Rising Sun -- The Gunseibu government -- Japanese policies towards indigenous peoples -- Japanese attitudes towards the Chinese -- 'Guests' of His Imperial Majesty The Emperor of Japan -- The Impact of Japanese Policies on Sarawak's Inhabitants -- On the indigenous peoples -- On the Chinese community -- On the European Community -- The Japanese Period and Its Effects on Post-War Developments -- Facing the quisling problem -- The decline of traditional native leadership -- The straining of inter-ethnic relations -- The issue of collaboration and Chinese-native relations -- Collaboration and Chinese communal leadership -- Sarawak Chinese nationalism and the emergence of Leftist elements -- Transformation or continuity? -- A Brief History of Kuching, Dec[ember] [19]41-Sep[tember] [19]45.
Includes bibliographical references (pages 133-141) and index.
Keywords: 1941-1945; Sarawak (Malaysia) -- History -- Japanese occupation, 1941-1945.; Malaysia -- Sarawak